Shroud of eternity - Goodkind, Terry (Goodkind, Terry. Nicci chronicles, 2018)
The formidable sorceress, Nicci, and her companions the newly powerless Nathan and the youthful Bannon set out on another quest after driving ruthless Norukai slavers out of Renda Bay. Their mission is to restore Nathan's magic and, for Nicci, save the world. Guided by the witch-woman Red's mysterious prophecy, the trio makes their way south of Kol Adair towards a wondrous city shrouded behind time, Ildakar. But the grotesque omens on their path to Nathan's salvation - severed Norukai heads on pikes, a genetically modified monster and a petrified army of half a million - are just a taste of the unimaginable horrors that await within the Shroud of eternity.